Rethinking of Hryhoriy Skovoroda’s Legacy in the 21st Century Publishing - Levytska, Oksana (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2022)
The article is dedicated to a review of the works by Hryhoriy Skovoroda published in Ukraine over the past two decades. Interdisciplinary studies that employ literary criticism and book publishing methodology have been applied to systematize the editions that were released between 2000 and 2022. A significant contribution to the publishing of Skovoroda’s legacy is The Complete Academic Edition of Hryhoriy Skovoroda’s Works edited by Professor Leonid Ushkalov (2010). In the focus of the study are also important editions of the previous years, such as the first complete translation of the author’s works into Ukrainian literary language and its subsequent new editions. In terms of the range of the assortment, the following editions should be noted: Hryhoriy Skovoroda. Selected Works (Terra Incognita, 2017), Literary Works and Our Life – A Journey (Apriori), SkorovoroDAR. Life, Creativity, Legacy (Shkola Publishing House). A significant share of the editions published are texts by Skovoroda that are studied in schools, i.e. pupils are reading them in translations into modern Ukrainian language or as adapted texts for children of different age groups. Such editions can be found in the repertoire of such publishing houses as Shkola, Apriori, Family Leisure Club, Ranok, Vivat, Chas Maistriv and others. Contemporary editions tend to have quality visual presentation, graphic story and modern illustrations. Skovoroda’s texts have also received unique illustrative accompaniment done by Agrafka Art Studio, Anna Sezon, renowned artist Oleksandr Roitburd, Marysia Rudska and others for the format of collector’s or gift editions. The research also covers the Russian-language editions of Skovoroda’s works published in Ukraine as well as musical and facsimile editions. A review of the editions allows for tracing specific trends in the publications of Skovoroda’s texts and the issues of preparing them for publication. The article is accompanied by a bibliography of editions of Skovoroda’s works that have been selected for analysis.